2020
DOI: 10.1002/iub.2432
|View full text |Cite
|
Sign up to set email alerts
|

Novel therapeutic regimens for urethane‐induced early lung cancer in rats: Combined cisplatin nanoparticles with vitamin‐D3

Abstract: Lung cancer remains incurable; therefore, novel therapeutical approaches are of great demand. This study was designed to investigate the effectiveness of cisplatin nanoparticles combined with vitamin-D 3 on urethane-induced early lung cancer in rats and to clarify the underlying signaling mechanisms. Early lung cancer was induced in male Wistar rats by urethane. Rats were divided into six groups: I-control, II-cancer untreated, III-cancer + free cisplatin, IV-cancer + cisplatin nanoparticles, V-cancer + free c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 70 publications
0
6
0
4
Order By: Relevance
“…Our lung cancer model was similar to that of Radwan et al [36], who used four intra-peritoneal injections of EC at a dosage of 0.375 g/kg over 12 weeks with a 3-week gap between treatments to cause lung adenocarcinoma in rats. After twenty weeks of EC administration, Janker et al [22] found that three times of EC injections (1 mg/gm) a week significantly increased the number of tumor nodules in mice compared to a single injection, even though there was no death or morbidity and a 100% tumor incidence rate.…”
Section: Discussionmentioning
confidence: 96%
“…Our lung cancer model was similar to that of Radwan et al [36], who used four intra-peritoneal injections of EC at a dosage of 0.375 g/kg over 12 weeks with a 3-week gap between treatments to cause lung adenocarcinoma in rats. After twenty weeks of EC administration, Janker et al [22] found that three times of EC injections (1 mg/gm) a week significantly increased the number of tumor nodules in mice compared to a single injection, even though there was no death or morbidity and a 100% tumor incidence rate.…”
Section: Discussionmentioning
confidence: 96%
“…Urethane is usually administered intraperitoneally or intravenously at doses ranging from 0.5 to 2 g/kg and can induce tumors within 6 to 12 months. Urethane-induced liver tumors are highly heterogeneous and can be classified into different histological subtypes, such as trabecular, pseudoglandular, and scirrhous [ 54 ].…”
Section: Examples Of Chemical Carcinogens In Mouse Cancer Modelsmentioning
confidence: 99%
“…Объектом исследования служил тимус. Количество животных, указанное в опытных группах, соответствует числу крыс, у которых через 90 дней после однократного введения уретана были обнаружены изменения в ткани легких в виде дисплазии альвеолярного эпителия, верифицированные классическими общегистологическими методами исследования [25].…”
Section: материал и методы исследованияunclassified
“…Уретан-индуцированный канцерогенез участвует в развитии как доброкачественных, так и злокачественных опухолей, главным образом опухолей легких, и считается ценной экспериментальной моделью аденокарциномы человека. При внутрибрюшинном введении уретана крысам индуцируется развитие аденомы легких [25]. Уретан превращается ферментом CYP2E1 цитохрома Р450 в винилкарбамат, что приводит к образованию эпоксида (винилкарбаматный эпоксид), который ковалентно связывается с ДНК и может привести к неправильному включению оснований во время репликации ДНК, что приводит к точечным мутациям [17,19].…”
Section: Introductionunclassified